Pengembangan kampung kota sebagai salah satu alternatif tujuan wisata minat khusus - Paulus Bawole (ARTEKS : Jurnal Teknik Arsitektur, 2020)
The development of urban kampong as one the alternatives special interest tourism Many people are interested in going to urban areas, because of the economic opportunities offered by city facilities. When cities grow in size and population, the harmony between the spatial, social, environmental aspects of the city and its inhabitants become very important. The formation of urban kampong settlements which are mostly inhabited by low-income communities is an integral part of the city's growth process. In general, people living in settlements do not have social power, less economic resources and physical ability to struggle to live in the city. They must be creative in handling minimal infrastructure facilities in settlements. The strategy of developing Urban Kampong into tourism destination is the process of developing urban kampong that focus on community empowerment through the construction of physical infrastructure. Therefore, this approach involves learning the local knowledge not only from the community leaders but also from all community members. This research will share the experience on how to empower communities living in urban kampong settlement in order to develop their housing areas into special interest tourism destinations.